Malignant ectomesenchymoma of the nasal cavity - Channappa N Patil; Sanju Cyriac; Urmila Majhi; Rejiv Rajendranath; T G Sagar (Indian Journal of Medical and Paediatric Oncology)
Malignant ectomesenchymomas are rare tumors. This tumor affects predominantly young children. Most common site is head and neck. A multi modality approach should be appropriate for this soft-tissue tumor. We present a 43 year old female with malignant ectomesenchymoma of the nasal cavity.